Co-inclusion: problematising binary understandings of social inclusion. (4th May 2022) - Polymenakou, Eva; Fay, Richard
ABSTRACT: This paper responds to a gap between theorists' bilateral understandings of social inclusion and the more unilateral understandings available to refugee support practitioners. We argue that scholarly work on social inclusion does not consistently reflect intercultural conceptualisations of societies as emergent spaces continually coming into being through the participation of all their members and bilateral understandings can institutionalise 'local/newcomer' power asymmetries. Our intercultural field can learn from the concept of co-inclusion which encapsulates key tenets of intercultural thinking and promotes a horizontal, collective, ongoing process of social inclusion that involves all members of a given society.